Analysis of Financial Factors on Dividend Policy of Manufacturing Companies - Titin Maryana; Hasbullah Hasbullah; Maria Septijantini Alie; Armalia Reny WA; Eka Travilta Oktaria; M. Nasir (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study analyzes the effect of liquidity, firm size, and profitability on dividend policy in manufacturing companies, specifically in the basic and chemical industry subsector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Methodology/Approach: This study uses a quantitative approach. The population consists of 75 companies with 375 firm-year observations, and the sample includes 15 companies observed over five years (75 samples). Data were collected by reviewing annual financial reports. Data analysis was conducted using multiple linear regression with the help of SPSS software. Results/Findings: The findings show that liquidity (CR), firm size (SIZE), and profitability (ROA) have positive and significant effects on dividend policy (DPR). Liquidity, firm size, and profitability also have positive and significant effects on dividend policy. Conclusions: The study concludes that higher liquidity, larger firm size, and greater profitability contribute to the improvement of dividend policy among manufacturing companies in the basic and chemical industry subsectors in Indonesia. Limitations: This study is limited to manufacturing companies in the basic and chemical industry subsector listed on the IDX, with the observation period restricted to 2020–2024. Contributions: This study contributes to the field of financial management by providing empirical evidence on how liquidity, firm size, and profitability affect dividend policy. The results are useful for academics, investors, and company managers to understand dividend decisions.